Unplugged Coding Integration Improves Computational Thinking and Collaboration: Integrasi Unplugged Coding Meningkatkan Computational Thinking dan Kolaborasi Siswa - Sari, Novita Wulan; Handoyo, Eko; Sumartiningsih, Sri (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The integration of 21st-century competencies, particularly computational thinking and collaboration, remains a central priority in primary education. Specific Background In practice, elementary education encounters structural constraints such as digital inequality and the abstract nature of science content, which limit the effective development of these competencies through conventional instruction. Knowledge Gap Existing studies rarely synthesize how educational game–based unplugged coding simultaneously supports computational thinking and collaborative skills within primary-level science learning. Aims This study conducts a systematic literature synthesis to examine the integration of computational thinking and collaboration through educational game media using unplugged coding approaches. Results Based on 20 selected articles following PRISMA 2020 procedures, findings indicate that unplugged coding significantly increases computational thinking performance by approximately 25%–42% compared to traditional approaches, while collaborative integration strengthens social interaction and active participation. Additionally, this approach supports conceptual understanding of abstract science topics by facilitating accurate mental model construction. Novelty The study identifies a synergistic learning configuration combining physical activity, algorithmic rule structures, and group interaction as a unified pedagogical system rather than isolated instructional elements. Implications These findings highlight unplugged coding as an inclusive, scalable, and pedagogically aligned strategy for strengthening computational thinking and collaboration in primary education, particularly under conditions of limited digital infrastructure. Highlights• Unplugged learning design demonstrates measurable gains in logical problem structuring• Cooperative gameplay strengthens student engagement and social interaction patterns• Physical simulation supports deeper conceptual reasoning in abstract science topics KeywordsComputational Thinking; Collaboration; Unplugged Coding; Educational Games; Elementary Education